ENVIRONMENTAL GEOCHEMISTRY AND SUSTAINABLE DEVELOPMENT: CASE STUDIES FROM GREECE - Argyraki, A. (Bulletin of the Geological Society of Greece, 2016)
The contribution of environmental geochemistry to sustainable development is discussed through the presentation of different case studies from Greece. The aim is to demonstrate the impact of geochemistry to a variety of societal and economic areas such as the sustainable exploitation of natural resources, the assessment of environmental problems within cities and the sustainable remediation of contaminated land. Several examples of completed and ongoing research are provided including a pre-mining survey in Skouries, Chalkidiki, a geochemical background study in an area of serpentine, agricultural soil in Atalanti, the urban soil geochemistry of Athens and the use of natural minerals as amendments for the remediation of contaminated land. The paper concludes with some facts on opportunities and obstacles to development in the field of environmental geochemistry in Greece under the current economic crisis conditions.